Endomysial antibody-negative coeliac disease: clinical characteristics and intestinal autoantibody deposits. Issue 12 (29th March 2006) - Salmi, T T; Collin, P; Korponay-Szabó, I R; Laurila, K; Partanen, J; Huhtala, H; Király, R; Lorand, L; Reunala, T; Mäki, M; Kaukinen, K
Abstract : Background: Some patients with untreated coeliac disease are negative for serum endomysial autoantibodies (EmA) targeted against transglutaminase 2 (TG2). Aims: To evaluate the clinical and histological features of EmA-negative coeliac disease, and to examine whether EmA-equivalent autoantibodies against TG2 can be seen in the small-bowel mucosa when absent in serum. Patients: Serum EmA was studied in 177 biopsy-proved specimens from adult patients with coeliac disease. 20 patients with intestinal diseases served as non-coeliac controls; three had autoimmune enteropathy with villous atrophy. Methods: Clinical manifestations, small-bowel mucosal morphology, intraepithelial inflammation and TG2-specific extracellular immunoglobulin A (IgA) deposits were investigated in both serum EmA-negative and EmA-positive patients. Results: 22 patients with IgA-competent coeliac disease were negative for serum EmA. Three of these had small-bowel lymphoma. Patients with EmA-negative coeliac disease were older, had abdominal symptoms more often, and the density of γδ+ intraepithelial lymphocytes in their intestinal mucosa was lower than in EmA-positive patients; otherwise the histology was similar. All serum EmA-negative patients with coeliac disease, but none of the disease controls, had gluten-dependent mucosal IgA deposits alongside TG2 in the small-bowel mucosal specimens. In vivo deposited IgA was shown to be TG2-specific by its ability to bind recombinant TG2. Conclusions: Negative serum EmA might be associated with advanced coeliac disease. TG2-targeted autoantibodies were deposited in the small-bowel mucosa even when absent in serum. This finding can be used in the diagnosis of seronegative coeliac disease when the histology is equivocal. It may also be helpful in the differential diagnosis between autoimmune enteropathy and coeliac disease.